The Earliest History of the Christian Gathering Origin, Development and Content of the Christian Gathering in the First to Third Centuries - Alikin, Valeriy A. (Brill, 2010)
Using recent insights into the nature of early Christian communities as religious associations, this book offers a new reconstruction of the origins and development of the weekly Christian gathering and its constitutive elements; based on an analysis of all available evidence from the first three centuries.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Religion / Theology; Religion; Electronic books